Mouse Lyt-2 antigen: evidence for two heterodimers with a common subunit. - Jay, G (1982)
Immunoprecipitation of [35S]methionine-labeled extracts of BALB/c thymocytes with mouse Lyt-2.2 monoclonal antibody yielded three components with subunit Mrs of 37,000, 32,000, and 28,000 on NaDodSO4/polyacrylamide gel in the presence of a reducing agent. Two-dimensional polyacrylamide gel analysis revealed that, in the absence of a reducing agent, the three polypeptide chains exist in the form of two heterodimers, each consisting of one molecule of a Mr 28,000 subunit covalently associated through disulfide bonds with either one Mr 37,000 subunit or one Mr 32,000 subunit. These two molecular structures are present in about equimolar ratios in the immunoprecipitate. Immunoautoradiographic analysis after electrophoretic transfer of proteins from a NaDodSO4/polyacrylamide gel to a nitrocellulose membrane indicated that the Lyt-2.2 determinant detected by the monoclonal antibody resides on the Mr 28,000 component, the common subunit of both heterodimeric structures. Lyt-2 precipitated from extracts of different T-cell growth factor-dependent cloned T-cell lines also showed similar structures, although the exact apparent Mrs of the respective components varied somewhat. The structure of the Lyt-2 antigen is of importance, particularly in the light of recent suggestions that it may be involved in the construction of one class of T-cell receptors.